Nectar, Floral Morphology and Pollination Syndrome in Loasaceae subfam. Loasoideae (Cornales) - ACKERMANN, MARKUS (Oxford University Press, 2006)
• Background and Aims Loasaceae subfam. Loasoideae are mostly distributed in South America (sea level to over 4500 m) with a wide range of animals documented as pollinators. The aim was to investigate correlations between nectar parameters, flower morphology, pollination syndrome and phylogeny. • Methods Nectar was collected from 29 species from seven genera in the subfamily. Concentration and volumes were measured and the amount of sugar calculated. Correlations of nectar data were plotted on a ternary graph and nectar characteristics compared with flower visitors, floral morphology and phylogenetic data. • Key Results Sugar concentrations are generally higher than reported for most plant families in the literature. The species investigated can be roughly grouped as follows. Group I: plants with approx. 1·5(–3·5) µL nectar with (40–)60–80 % sugar and 0·19–2 mg sugar flower(−1); with small, white, star-shaped corollas, pollinated by short-tongued bees. Groups II, III and IV: plants with mostly orange, balloon-, saucer-, bowl- or bell-shaped corollas. Group II: plants with approx. 9–14 µL nectar with 40–60 % sugar and 4–10 mg sugar flower(−1); mostly visited by long-tongued bees and/or hummingbirds. Group III: plants with 40–100 µL nectar with 30–40 % sugar and 14–36 mg sugar flower(–1), mostly visited by hummingbirds. Group IV: geoflorous plants with 80–90 µL with 10–15 % sugar and 8·5–12 mg sugar flower(–1), presumably visited by small mammals. Groups II and III include species visited by bees and/or hummingbirds. • Conclusions Pollinator switches from short-tongued bees via long-tongued bees to hummingbirds appear to have taken place repeatedly in the genera Nasa, Loasa and Caiophora. Changes in nectar amount and concentration appear to evolve rapidly with little phylogenetic constraint.